oxidative DNA damage and lipid peroxidation as markers of oxidative stress type 2 diabetic patients - AL-Aubaidy, hayder A.; El-Yassin, Hedef Dhafir; Hashim, hashim M.; AL-Shamma, Ghassan (Journal of the Faculty of Medicine Baghdad, 2008)
Background:type 2 diabetes mellitus is a chronic disease that is accompanied by  the production of free radicals which will ultimately increase the level of oxidative stress.